Before, During, and Beyond the Brillo Box: The Impact of Pop on the 1964 Edition of Duchamp's Readymades. (2nd October 2018) - Bailey, Bradley
Abstract : Marcel Duchamp's controversial decision to produce an edition of replicas of his best-known readymades in 1964 remains one of the more puzzling and unexpected moves in a career already identified with defiance and provocation. Duchamp's decision to sell reproductions of the readymades challenged his own customarily anti-commercial approach to art, eliciting unfavorable responses from his contemporaries and followers. In this article I intend to demonstrate that the 1964 edition of the readymades was the culmination of a series of events that motivated Duchamp to more firmly establish himself as the foundation of the Pop art movement. Duchamp's decision to create an edition of the readymades also came shortly after he first met Andy Warhol in Pasadena in 1963, at which time Duchamp would certainly have been thinking about his legacy and how it would come to measure up against the new generation of appropriation artists. It is also impossible to consider these replicas without taking into account that they were produced during Pop's meteoric rise. With this study, I hope to emphasize that the reciprocal impact of Pop on Duchamp is just as important in shaping our current understanding of the readymade.